Poppy Redfern and the fatal flyers : [large type] a woman of World War II mystery - Arlen, Tessa (Arlen, Tessa. Woman of World War II mystery, 2021)
"It is the late autumn of 1942. Our indomitable heroine Poppy Redfern is thoroughly immersed in her new job as a scriptwriter at the London Crown Film Unit, which produces short films featuring British civilians who perform acts of valor and heroism in wartime. After weeks of typing copy and sharpening pencils, Poppy is thrilled to receive her first solo script project- a ten-minute film about the Attagirls, and Poppy is enthralled to meet these glamorous wartime heroines. Britain is so overwhelmed by military losses that the Air Transit Auxiliary has been formed to train civilians to pilot fighter and bomber planes from factories to military airfields all over Britain. One hundred and sixty eight of them are women. They are known as the Attagirls, and Poppy couldn't be more excited to spend time with these amazing ladies. But she never expects to see two of the pilots die in seemingly preventable 'accidents.' Poppy and her handsome American fighter pilot Griff believe foul play may be at work and they soon realize that a murderer with a desire for revenge is already looking for a new victim"--